Hubungan Status Gizi Balita terhadap Tingkat Kecemasan Ibu yang Memiliki Balita di Kelurahan Karsamenak Kecamatan Kawalu Kota Tasikmalaya - Wawan Rismawan; Shofi Hanifah A; Ani Nur Ulfah (STIKes Persada Husada Indonesia, 2015)
The main challenge in the development of a nation is to build the human resources quality, healthy,intelligent and productive, that can measured by the Human Development Index (HDI). Low HDI was influencedof low nutritional status have an impact on population health. Nutritional status of infants should be veryguarded and serious concern of the parents, because in case of malnutrition during this period will causeirreversible damage. Malnutrition have fatal impact on brain development. Anxiety can be accompanied byphysical symptoms such as headache, rapid heart beat, chest tightness, abdominal pain, restless and unable tosit still, unable to do anything despite the directives.. The purpose of this study was to determine the associationbetween nutritional status of mothers and children against anxiety levels who have children in Sub KarsamenakKawalu District of Tasikmalaya City. This research was conducted in June 2016 in the Village KarsamenakKawalu District of Tasikmalaya City with a sample of 50 mothers and their toddlers. This type of research is acorrelation study by using cross sectional approach. Data collection tool is a questionnaire used the HamiltonRating Scale for Anxiety (HRS-A), data used in the form of primary data and secondary data. Processing datawas using SPSS for windows release 21. The analysis used were univariate and bivariate Spearman rank (rho),test indicated that p value is 0,012 and coefficient correlation is 0,354. The conclusion was there is relationshipbetween nutritional status of children and anxiety mothers who have children with a low correlationKeywords: nutritional status of children, mother’s anxiety, Hamilton Rating Scale for Anxiety (HRS-A)